A Spatial Analysis Of The Knowledge - Based Economy In Poland - Strożek, Piotr (Comparative Economic Research. Central and Eastern Europe, 2014)
The article presents a spatial analysis of the knowledge-based economy in Poland in regional terms in 2003 and 2011. Nowadays, knowledge is regarded as one of the factors of production besides land, labor and capital. The ability to create, collect and effectively use knowledge contributes to the generation of innovation, acquiring long-term competitive advantages and economic success. Polish provinces are the basic territorial units, on which the calculations have been carried out. The period of time was purposely chosen to determine the impact of Polish accession to the European Union and the possibility of using the Structural Funds in the development of local economies based on knowledge. The purpose of this article is to identify disparities in the use of knowledge in socio-economic life in the Polish provinces. The study was conducted using a taxonomic measure of development (one of the tools of multidimensional comparative analysis). Classification of provinces was constructed on the basis of KEI (Knowledge Economy Index) and KI (Knowledge Index) which are used by the World Bank in Knowledge Assessment Methodology (KAM). The division into four pillars (i.e. The Economic Incentive and Institutional Regime, The Innovation System, Education and Human Resources, Information and Communication Technology) attempts to explain the relationship between the factors of development.